Maternal Mortality Rate Reduction Program Implementation During The Coronavirus Diseases 19 Pandemic in West Java Province - Siagian, Marion (Contemporary Public Administration Review, 2023)
Maternal mortality cases during the Covid-19 pandemic in West Java Province have increased. This study aims to describe the maternal mortality reduction program during the Covid-19 pandemic in West Java Province. This research was conducted using a literature review method to provide an overview of the research problem. During the Covid-19 pandemic in West Java, Covid-19 became the most significant cause of death among pregnant women. The program to reduce the mortality rate of pregnant women due to Covid-19 in West Java was carried out to follow up on central government programs including the preparation of regulations related to the protection of mothers and children, the implementation of the vaccination program for pregnant women, PCR examination of pregnant women a week before the estimated date of birth and pregnant women who experience symptoms similar to Covid-19, increasing readiness for childbirth handling at the public health center and referrals to hospitals as well as efforts to improve the health of pregnant women through programs 3M and 5M. The program to reduce the mortality rate of pregnant women during the Covid-19 pandemic in West Java Province has been implemented well. More research is needed to assess the success rate of the program.